2005
DOI: 10.1002/j.1556-6678.2005.tb00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Power, Control, and Being Nice: Aggression in Adolescent Girls' Friendships

Abstract: The relationship between gender role identity and relational aggression was examined. Fifty-two girls (mean age = 15 years; 70% White, 30% non-White) from the mid-Atlantic U.S. completed the Relational Aggression Scale and the Bem Sex-Role Inventory (S. L. Bem, 1981a). Use of relational aggression friendships among adolescent girls significantly predicted 9.9% of the variance for the high feminine variable. Focus group interviews were used to complement the quantitative study. Specific themes are identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 9 publications
3
58
1
8
Order By: Relevance
“…Some studies have tried to focus on this issue in schools, specifically. Research has identified how girls from minority backgrounds often struggle with school material and assumptions of femininities centred in 'whiteness' (Crothers, Field & Kolbert, 2005;Carter, 2007), and experience educational difficulties that may be specific to the girls' backgrounds and cultural experiences of schooling (Smith-Hefner, 1993). Research also draws attention to the difficulties for some minority girls in adapting cultural practices to physical education demands (Hamzeh & Oliver, 2012) and the diversity in the formation of identities of girls from multiple backgrounds co-existing and trying to combine their identities (Joseph, 2010).…”
Section: Multiculturalism and Gender Equality -Combined Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have tried to focus on this issue in schools, specifically. Research has identified how girls from minority backgrounds often struggle with school material and assumptions of femininities centred in 'whiteness' (Crothers, Field & Kolbert, 2005;Carter, 2007), and experience educational difficulties that may be specific to the girls' backgrounds and cultural experiences of schooling (Smith-Hefner, 1993). Research also draws attention to the difficulties for some minority girls in adapting cultural practices to physical education demands (Hamzeh & Oliver, 2012) and the diversity in the formation of identities of girls from multiple backgrounds co-existing and trying to combine their identities (Joseph, 2010).…”
Section: Multiculturalism and Gender Equality -Combined Responsesmentioning
confidence: 99%
“…Furthermore, it is not surprising that Audra would identify being a 'tomboy' as more desirable than 'manly' as being a 'tomboy' is still being 'childish' and capable of change while being 'manly' is possibly more permanent. Feminists have studied how girls negotiate as well as resist dominant constructions of femininity (Caudwell, 2011) and while being a tomboy is among the more common ways schoolgirls are 'doing' femininity, it is still a way to transgress gender norms that sometimes results in social punishment, as often happens to girls who engage in 'traditionally masculine forms of relating' (Povey, 2004a;Crothers et al, 2005;Ringrose & Renold, 2010). Audra, for instance, has experienced 'group punishment', through 'name calling' and 'gossip' even though she was engaging in a more valued set of behaviours when compared to more traditional femininities (Martino & Pallotta-Chiarolli, 2005).…”
Section: Boys As Friendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, black women do not do any of these things-I never had to learn to smile when I did not mean it--(2010, p. 118) While it seems that Black women may be masking their feelings in other ways, it appears that anger is not prohibited. One theory is that because Black women are allowed to be angry in ways that White women are not they may utilize less relationally aggressive behaviors (Crothers et al, 2005). However, as noted in the earlier discussion of intersectionality, while there is growing attention to relational aggression in culturally diverse samples, we have been testing those samples based on a set of norms developed with White women.…”
Section: The Role Of Culture In Relationally Aggressive Behaviorsmentioning
confidence: 99%
“…Another possibility that has been proposed is that women of color do experience relationally aggressive behaviors in their relationships, but do not consider them as harmful as other participants (Crothers, Field, & Kolbert, 2005). However, in a clinical study, it was found that female African American college women did experience relational aggression, and while there were only a small number of participants who reported victimization, the study showed a positive correlation between being the victim of relationally aggressive behavior and depression (Gomes et al, 2009).…”
mentioning
confidence: 99%